Imagens (des)contínuas: representações visuais do cangaceiro Antônio Silvino no cordel - Rodrigues Filho, José (CEM – Cultura, Espaço & Memória, 2020)
This article carries out a study of visuality related to the cangaceiro Antônio Silvino in cordel literature. The paper studies pictures present in the covers of seven flyers about Antônio Silvino published in the first half of the 20th century. Besides the cordel’s, the article dialogues with pictures published in two magazines: O Malho and Flor de Liz. The paper adopts two theoretical concepts: visual culture and pathosformenl which are used with the main intention of observing the visual continuities and discontinuities around the image of the cangaceiro Antônio Silvino in cordel literature. It was possible to observe that certain elements, «gestures» and signs of a culture and society do not isolate and end in themselves in their historical time, but they overcome the barriers of temporalities, establishing connections and interconnections with images of other supports, contexts and historical temporalities. Likewise, it is possible to understand that the reutilization of pictures follows interests that pervade the editorial field, where authors and editors transit in memories and places that offer a visual repertoire that is taken to the construction of representations and visual narratives present in cordel literature.